Pengembangan LKPD Berbasis Komik pada Materi Bilangan Bulat untuk Meningkatkan Pemahaman Matematis Siswa Kelas VII - Aini, Jumratul; Astuti, Reni; Abdillah, Abdillah (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to produce a product in the form of a comic-based worksheet that is seen from the level of validity, practicality and effectiveness so that it can be used in the learning process. The type of research used in this research is Research and Development (R&D) with a Borg and Gall research design. This research was carried out at SMP Negeri 1 Tanah Pinoh, Melawi, West Kalimantan with research subjects of 30 class VII students. The instruments used in this research were material and media validation sheets, teacher and student response questionnaires, and mathematical understanding posttest sheets. From the research results, it was found that the comic-based worksheet that was developed was suitable for use in the learning process with the criteria "valid" with the validity of the material reaching 81.98% and the validity of the media reaching 82.22%, the level of practicality with the criteria "very practical" as indicated by the questionnaire Student responses reached 87.88% and questionnaire responses given by teachers reached 90.90%. The level of effectiveness with the criteria "very effective" is based on the minimum criteria completion value (KKM) determined by the school